2013
DOI: 10.1016/j.resp.2013.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase inhibition and regional sympathetic nerve discharge: Implications for peripheral vascular control

Abstract: Neuronal nitric oxide (NO) synthase (nNOS) inhibition with systemically-administered S-methyl-L-thiocitrulline (SMTC) elevates mean arterial pressure (MAP) and reduces rat hindlimb skeletal muscle and renal blood flow. We tested the hypothesis that those SMTC-induced cardiovascular effects resulted, in part, from increased sympathetic nerve discharge (SND). MAP, HR, and lumbar and renal SND (direct nerve recordings) were measured in 9 baroreceptor (sino-aortic)-denervated rats for 20 minutes each following bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
3
1
0
Order By: Relevance
“…Our study also found that MAP increased at 5 minutes of resuscitation when specific neuronal NOS inhibitors SMTC or ARL17477 were added to 7.5% NaCl ALM, which was opposite to 7.5% NaCl ALM + L-NAME ( Figure 5 A ). These data support Copp et al's 51 earlier studies showing that SMTC increases peripheral vasoconstriction in animal models. Similarly, as previously mentioned, MAP increased in the presence of the selective guanylyl cyclase inhibitor ODQ, which is consistent with the study of Olson et al 29 who showed that it reversed NO-induced vasorelaxation.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found that MAP increased at 5 minutes of resuscitation when specific neuronal NOS inhibitors SMTC or ARL17477 were added to 7.5% NaCl ALM, which was opposite to 7.5% NaCl ALM + L-NAME ( Figure 5 A ). These data support Copp et al's 51 earlier studies showing that SMTC increases peripheral vasoconstriction in animal models. Similarly, as previously mentioned, MAP increased in the presence of the selective guanylyl cyclase inhibitor ODQ, which is consistent with the study of Olson et al 29 who showed that it reversed NO-induced vasorelaxation.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies from our laboratory indicate that nNOS inhibition with systemic SMTC administration in healthy sedentary rats evokes global hemodynamic effects (i.e., increases in MAP) without alterations in renal or lumbar sympathetic nerve discharge [7]. These results support that systemically administered SMTC modulates regional nNOS-mediated vascular control rather than centrally-derived sympathetic vasoconstriction.…”
Section: Discussionsupporting
confidence: 76%
“…Ϫ -NO reduction is that NOS reliance is avoided, with NO 2 Ϫ being reduced to NO in environments of low O 2 /pH via interactions with deoxyhemoglobin, tissue and vascular myoglobin, xanthine oxidoreductase, and aldehyde dehydrogenase. Furthermore, by experimental blockade of endogenous production of NO from eNOS and nNOS pharmacologically [nitro-L-arginine methyl ester (L-NAME; eNOS and nNOS) and S-methyl-L-thiocitrulline (SMTC; nNOS)], blood flow is reduced independent of any increases in sympathetic activity/vasoconstriction (11,12,29,30). The present results clearly demonstrate that NaNO 2 increases baseline (resting) PO 2 mv and suggest strongly that the Values are means Ϯ SE.…”
Section: Microvascular Oxygen Pressure (Po 2 Mv) Dynamicssupporting
confidence: 61%